Pre-service EFL teachers’ perceptions of oral corrective feedback for reflective thinking and metacognitive awareness in microteaching - Abdullah Kafabih; Rozanah Katrina Herda; Bazilah Raihan Binti Mat Shawal; Natalya Andreevna Karelina (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study aimed to examine pre-service EFL teachers’ perceptions of oral corrective feedback (OCF) in relation to their reflective thinking and metacognitive awareness during microteaching activities. Using a quantitative descriptive survey design, data were collected from 64 participants at an Indonesian public university via a validated questionnaire and analyzed through descriptive statistics and Likert-scale interpretation frameworks. The results indicate that participants perceived OCF as supporting reflective thinking and metacognitive awareness, particularly when feedback included clear explanations, contextual relevance, and peer interaction. Participants reported using feedback to evaluate instructional choices, set learning goals, and regulate their teaching strategies. Conversely, lower confidence in self-correction highlighted a continued reliance on external guidance during this developmental stage. This study extends existing literature by positioning OCF not merely as a performance correction tool but as a cognitive prompt that initiates a sequential pathway toward self-regulated learning. The findings offer practical guidance for teacher educators to design feedback practices that deliberately scaffold reflective inquiry and gradually build autonomous evaluative judgment in novice teachers.